Estrategias para el mejoramiento la cadena de suministro del carbón en Norte de Santander, Colombia (2015)
This article aims to structure and characterize the supply chain of coal in Norte de Santander, identifying the main factors influencing the improvement of it. In this sense, an information search on secondary sources is performed to conceptualize the main contributions and functionality of logistics and supply chain management in the coal sector. With the collected data the different stages and actors involved in the chain of supply of coal are structured and characterized, and the most important strategies to achieve world-class performance in the supply chain are identified. As a result, it is recommended to adopt a supply chain model in the coal sector in Norte de Santander, and also implement strategies related to demand assurance, appropriate infrastructure, modernization of production processes, associativity, legal accompaniment, availability of supplies, long-term partnerships, supply stability, reduced energy costs and environmental sustainability.